ALLEGORICAL SYMBOLIC REPRESENTATION IN THE PERFORMING AND VISUAL ARTS: USING THE EAGLE AS A CONCEPT - Ugochukwu, Ephraim; Ogunwo, Bolaji; Ogbonnia, Egwu Ifeanyi; Emezue, Nefertiti Nneoma; Aigbonoga, Stephen Oshiomah; Lawal, Abdullahi; Idam, Otuu Ogobuchi; Obiukwu, Chinatu Regina; Obiukwu, Chinelo Rophina (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The paper examined the allegorical, symbolic representation of form in the visual and performing arts. When proverbs are used to express truth, especially when one cannot decode and sense the danger ahead, all would have been lost, the milk, like it is usually said, would have been spilt. All over the world, proverbs are used as simple idioms to express truth, based on common sense or experience. Scholars believe that proverbs are tools for thinking and communication. Proverbs are deployed as philosophy which keeps the mind in check, most times when human beings are praised, referred to as brave animal like the lion, tiger or an eagle among others, there is always this excitement, happiness or joy that over whelms and takes-over the individual, but when one is referred to as a lesser animal like goat, chicken, rat or even a cockroach for example, the reverse is always the case. The paper examined the eagle's great attributes. Some artworks can be considered to have allegorical content because they communicate in the same way as verbal metaphors. Some pertinent questions were asked, which gave rise to the creative work. Data was gathered through an exploratory conceptual study (a document-based qualitative study approach), relevant primary and secondary sources, electronic media, and other sources were consulted. This also led to solving environmental problems and enhancing the environment. The research created a three-dimensional, realistic sculpture piece of the eagle, and equally analyses the eagle and its other great attributes. The paper concludes that exploring idiomatic expressions, reading meaning into the daily use of words, could inspire more creative works.